Analyze Production Potential of Several Local Upland Rice Lines - Sakka Samudin; Mustamin; Maemunah (Research Advances and Challenges in Agricultural Sciences Vol. 9, 2024)
Extreme weather events like excessive heat, heavy rain, and drought are brought on by climate change and result in global warming. Climate change affects agricultural production, notably rice crops, and results in harsh weather. Because it is becoming harder to utilize the area of paddy fields, one effort that can be made to boost the national food supply is by improving and expanding the upland rice farming area. This study aimed to analyze and ascertain the upland rice lines in the area’s production potential. The study was carried out on agricultural land in Tamarenja Village (Kalama backwoods), Central Sulawesi Province, about 200 meters above sea level, with latitudes of 00o26’51.5" South Latitude and 119o49’50.6" East Longitude. They began in August 2022 and continued through February 2023. Fifteen strains or varieties of upland rice were used in the study’s Randomized Block Design (RBD), which was repeated three times to create 45 trial plots. These strains or varieties included Untad I, Untad II, Untad III, Untad V, Uva Buya, Kalendeng, Pulu Tau Leru, Jahara, Buncaili, Delima, Dongan, Konta Island, Tako, and Situ Bagendit. Plant height, leaf length, tiller number, productive tiller number, panicle length, number of grains/panicles, harvest age, the weight of 1000 grains, and production were among the variables recorded. The collected data was analyzed using analysis of variance. Test results Least Significant Difference (LSD) of 5% indicated that all the lines used had higher plant height than the control (situ bagendit). The findings demonstrated that the Tako, Dongan, Pulu Tau Leru, Uva Buya, and Kalendeng strains produced better yields compared to the control variety.